A Comparative Study of Fintech Literacy between Generation Y and Generation Z - Nurhayati, Netti Siska; Yuliawati, Tia; Nugraha, Nugraha; Sari, Maya (Jurnal Ekonomi Manajemen, 2025)
This study examines whether significant differences in fintech literacy exist between Generation Y and Generation Z in the context of increasing digital financial transformation. The use of technology in the financial sector is known as financial technology (fintech). The purpose of this study is to determine whether there are differences in Fintech Literacy between generation Y and generation Z, given that these two generations absorbed internet technology in their youth to adulthood, in the mid-1990s to 2000s. In this study, Fintech Literacy refers to the Diffusion of Innovation (DOI) theory and the Technology Acceptance Model (TAM) conceptual model. In order to answer the research questions, questionnaires were distributed to 100 generation Y respondents and 183 generation Z respondents. Hypothesis testing was carried out using the Mann-Whitney Test, adjusted for the ordinal scale data form. The results of the hypothesis test show that there is no significant difference in Fintech Literacy between generation Y and generation Z. Beyond its empirical contribution, this study enriches the fintech literacy literature by demonstrating that generational differences may be less pronounced than commonly assumed, particularly when both cohorts are exposed to similar technological environments